ANALISIS BEBAN GEMPA TERHADAP KEKUATAN STRUKTUR BANGUNAN MULTI DEGRRE OF FREEDOME - Almufid Almufid (Universitas Muhammadiyah Tangerang, 2016)
Structural analysis is planned phases of a building, especially the high buildings. In the analysis of the structure required to facilitate the modeling calculations reflect actual conditions in the field, both in structure and in the loaded . Because almost all parts of Indonesia, including the earthquake-prone areas is a challenge for civil engineering planning in order to design earthquakeresistant buildings. Indonesia has many experienced tremendous earthquake Writing this proposal is intended to be able to know the strength and structure of the response Strength multi degree of freedome, on soft ground, located in Tangerang when worn earthquake lateral loads, analysis is done with the help of the SAP program in 2000 ver.15, to get the style - the style such as: the base shear force, lateral force level, rolling moment and lateral deviation. Dynamic analysis was conducted using the response spectrum analysis, mass modeling performed with a lump mass models, the sum of the response variance is reviewed with some combinations, such as: CQC, SRSs and ABSSUM. Keywords: Building Multi Degrre of Freedome, response spectrum analysis, dynamic loads, with the use of the method; CQC, SRSS, ABSSUM